Le Cycle pictural de la cour d’appel de Toulouse par Georges d’Espagnat (1942-1944) : un témoignage de la permanence d’une formule décorative - Coralie Machabert (In Situ)
In Toulouse Palace of Justice (courthouse), the “Cour d’Appel” preserves a pictorial ensemble dating from the 1940s that is now unknown. Despite its prestigious setting, the modest decoration, inaugurated in 1944 executed by Georges d'Espagnat, takes on another dimension in the distance of History.At a time when the genre was disappearing, the project was supported by influential institutional figures, first and foremost President Joseph Guérin. He personally got involved to finalise this programme initiated in the 1930s. The negotiations demonstrate the importance of relations between local actors and French governing bodies. In 1942, an allegory of protective Justice framed by a history of Toulouse judiciary was realised for the Great Staircase. Two paintings show in addition the prosperity of the regional land, agrarian and spiritual treasures. Two others in the “salle des pas perdus” (waiting room) exalt work and family.The selected painter is representative of the “art du Juste-Milieu”. He uses a measured style and a traditional iconography adapted with the period and the function of the place. This programme, typical of the esprit of the French Third Republic, testifies to the persistence of a decorative approach of justice buildings outdated at the time.